Biomarkers of muscle fatigue during exercise. Issue 3 (March 2016) - Finsterer, J.
Abstract : The physiologic background of exercise-induced muscle fatigue (EIMUF) is only poorly understood. Thus, monitoring of EIMUF by a single or multiple biomarkers (BMs) is under debate. EIMUF is mainly due to depletion of substrates, increased oxidative stress, muscle membrane depolarization following potassium depletion, muscle hyperthermia, muscle damage, impaired oxygen supply to the muscle, activation of an inflammatory response, or impaired calcium-handling. Dehydration, hyperammonemia, mitochondrial biogenesis, and genetic responses are also discussed. Since EIMUF is dependent on age, sex, degree of fatigue, type, intensity, and duration of exercise, energy supply during exercise, climate, training status (physical fitness), and health status (healthy/diseased), BMs currently available for monitoring EIMUF have limited reliability. Generally, wet and dry BMs are differentiated. Among dry BMS the most promising include measurement of the power output, measurement of speed, electrophysiologic and cardiologic parameters, and questionaires. Among wet BMs those most applicable to monitor EIMUF include serum lactate, oxidative stress parameters, and inflammatory markers. Though the physiology of EIMUF remains to be fully elucidated, some promising BMs have been recently introduced, which together with other BMs, could be useful in monitoring EIMUF. However, it is essential that reliability and applicability of each BM candidate is validated in appropriate studies.